2022
DOI: 10.5897/jaerd2022.1348
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of subsistence maize farmers on aflatoxin contamination and determinants for adoption of artisanal control technologies in Kitui, Kenya

Abstract: Widespread aflatoxin contamination of maize is a public health hazard in Sub-Saharan Africa and its management requires strategies which are implemented both at pre-and post-harvest stages of cereal production. This study aimed at assessing knowledge and practices for aflatoxin contamination of maize and factors associated with adoption of artisanal aflatoxin control technologies. A semistructured questionnaire was administered to 315 household heads that were practicing subsistence maize farming in Kitui, Ken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Produce stored on the bare ground encourages the growth of Aspergillus species that produce aflatoxins by increasing ambient humidity (Kaaya and Eboku, 2010). The findings support those of numerous authors who also reported that storing produce on the bare ground caused high levels of aflatoxins (Kyalo et al, 2022;Namubiru et al, 2022;Sahar et al, 2022) 4.2 Knowledge on aflatoxins and levels of total aflatoxins in maize, maize flour and beans.…”
Section: 1supporting
confidence: 76%
“…Produce stored on the bare ground encourages the growth of Aspergillus species that produce aflatoxins by increasing ambient humidity (Kaaya and Eboku, 2010). The findings support those of numerous authors who also reported that storing produce on the bare ground caused high levels of aflatoxins (Kyalo et al, 2022;Namubiru et al, 2022;Sahar et al, 2022) 4.2 Knowledge on aflatoxins and levels of total aflatoxins in maize, maize flour and beans.…”
Section: 1supporting
confidence: 76%
“…Te average household size was 6 persons, and the average land size owned by households was 2.6 acres, with the largest farm size holding being 20 acres. Te primary sources of income for households included crop agriculture and livestock farming (96%) with only a small proportion of respondents who were on salary employment [30].…”
Section: Demographic Characteristics Of Maize Farmersmentioning
confidence: 99%
“…Shelled maize grain was stored either in hermetic bags (44%), propylene bags (39%), and gunny bags (13%), while the remainder was stored without shelling. Fifty percent of maize farmers applied insecticides before maize storage, while the majority of farmers placed maize bags on wooden pallets during storage [30].…”
Section: Artisanal Afatoxin Control Technologies Adopted Bymentioning
confidence: 99%